Influencing factors of oncologic patient care management in a general hospital - Peiter, Caroline Cechinel (2016)
Aim: To present the factors that affect the management of nursing care to cancer patients in a general hospital located in Southern Brazil. Method: This is a qualitative study that used the Grounded Theory, with Strauss approach for data analysis. Fourteen participants have been interviewed through semi-structured interviews: six registered nurses, five nursing techinicians, one nutritionist, one psychologist and one person of patient’s Family, from August to October 2010. Results: As intervening factors, it was identified: management unit performed by nurses, cancer pain, the need for training, bonding with family, interpersonal relationships on the team, the non-specificity of the clinic, and the process of death. Conclusion: The general hospital professionals have difficulty in offering a specific and appropriate care to the cancer patient, reaffirming the importance of the support of continuing education, interdisciplinarity and job satisfaction.